2011
DOI: 10.1590/s0100-29452011005000089
|View full text |Cite
|
Sign up to set email alerts
|

Teores de carboidratos nas folhas e produção de limeiras ácida 'tahiti' aneladas e tratadas com ácido giberélico

Abstract: RESUMO-O objetivo do trabalho foi avaliar o efeito do ácido giberélico (GA 3 ) e anelamento de ramos sobre os teores de carboidratos nas folhas, a produção e o peso de frutos de limeira ácida 'Tahiti'. O delineamento experimental foi em blocos casualizados, com cinco repetições, em esquema fatorial 4x3. O primeiro fator foi a aplicação de GA 3 em quatro concentrações (0; 7; 14 e 21 mg/L -1 ), e o segundo, duas épocas de anelamento, no início e um mês após o florescimento, mais a testemunha sem anelamento. Veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
1
10
0
1
Order By: Relevance
“…The Thus, this result is corroborating with earlier studies that indicated that the inhibitory effect of GA 3 on the flower differentiation, preventing, or decreasing the production of flowers (Maia et al, 2010). With the application of GA 3 , the plant decreased the intake of assimilates involved in flowering (Serciloto et al, 2003), increasing the supply of carbohydrates to the fruits (Pereira et al, 2011).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The Thus, this result is corroborating with earlier studies that indicated that the inhibitory effect of GA 3 on the flower differentiation, preventing, or decreasing the production of flowers (Maia et al, 2010). With the application of GA 3 , the plant decreased the intake of assimilates involved in flowering (Serciloto et al, 2003), increasing the supply of carbohydrates to the fruits (Pereira et al, 2011).…”
Section: Resultssupporting
confidence: 90%
“…This result is due to the fact that, although the girdling had been performed still in the crop season, its effect lasted until the extemporaneous harvest, blocking the transport of photoassimilates through the phloem, from the aerial part to the roots, paralyzing the vegetative growth of plants (Pereira et al, 2010) and the reserves in the aerial part, as a consequence. Therefore, abscission of flower structures was reduced (Mehouachi et al, 2009;Pereira et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Após a abscisão natural de frutilhos, a competição dos drenos por carboidratos diminui, o que pode favorecer a elevação dos teores de amido nas folhas, pelo transporte das raízes (Mahouachi et al, 2009) ou pelo aumento nas taxas fotossintéticas no início do verão (Pereira et al, 2011;Ribeiro et al, 2012).…”
Section: Resultsunclassified